EFFECTIVENESS OF PEAR DECK IN ENHANCING COGNITIVE, BEHAVIOURAL, AND EMOTIONAL ENGAGEMENT IN ONLINE PHARMACOLOGY EDUCATION FOR NURSING STUDENTS: A SYSTEMATIC REVIEW - Saharin, Amizah; Mat, Samsiah; Ramli, Noorazura; Alias, Zahariah; Zakaria, Zaidah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The transition to online learning during and following the COVID-19 pandemic has accelerated the adoption of interactive educational technologies in nursing education, particularly for content-intensive subjects such as pharmacology. Pear Deck, an interactive slide-based response system, has emerged as a promising tool for fostering student engagement in virtual learning environments. This systematic literature review synthesises empirical evidence on the effectiveness of Pear Deck in enhancing cognitive, behavioural, and emotional engagement among nursing students in online pharmacology education. Guided by the PRISMA 2020 framework, a comprehensive search was conducted across Scopus, Google Scholar, and Semantic Scholar. Nineteen studies published between 2020 and 2025 met the inclusion criteria and were analysed using a thematic synthesis approach informed by the Population–Exposure–Outcome (PEO) framework. Although the primary focus was on nursing and pharmacology education, relevant studies from closely related health sciences and higher education. Contexts were included to address the limited availability of domain-specific research. The findings indicate that Pear Deck supports cognitive engagement through interactive questioning and retrieval practice, behavioural engagement through increased participation and attentiveness, and emotional engagement through reflective prompts and emotional check-in features. Instructor pedagogical readiness, structured lesson design, and student digital literacy emerged as key facilitators, while technological constraints and cognitive overload were identified as barriers. This review highlights Pear Deck’s pedagogical value in online nursing pharmacology education and provides evidence-based recommendations for educators and instructional designers.